Handgrip strength and phase angle predict outcome after bariatric surgery - Gerken, Andreas; Rohr-Kräutle, Kim-Kristin; Weiß, Christel; Seyfried, Steffen; Reißfelder, Christoph; Vassilev, Georgi; Otto, Mirko (Obesity surgery, 2021)
The amount of postoperative weight loss after bariatric surgery varies interindividually. The quality of the pre- and postoperative body composition is an important predictor of success. The aim of this study was to investigate the role of preoperative handgrip strength and phase angle (PhA) as predictors of sustained postoperative weight loss in order to assess the influence of body composition on the postoperative outcome after bariatric surgery.
Published online: 15 August 2020
Gesehen am 09.06.2021